Strategi Pengembangan Pulau Kelapan Desa Kumbung sebagai Destinasi Pariwisata Berkelanjutan - Ikhlas Makruf; Warisa Warisa; Intan Kurnia; Verbi Haryanto; Winarsih Winarsih; Depita Kirana; Ines Pratiwi; Zainul Arif Rosyadi; Muhammad Ali Bangsawan; Dewi Astri; Andesta Granitio Irwan (Jurnal Pengabdian Masyarakat Waradin, 2025)
Kelapan Island, located in Kumbung Village, has great potential as a sustainable tourism destination. Natural beauty, biodiversity, and unique local culture are the main attractions. This study aims to analyze the potential and development strategies of Kelapan Island as a sustainable tourism destination. The method used is a qualitative descriptive method including field observation, interviews with local people, and literature analysis. The results of the study indicate that community-based management, environmental conservation, and effective promotion can increase tourist attractions without damaging the ecosystem. In conclusion, Kelapan Island has great potential to develop as an economically profitable and sustainable ecotourism destination.